Cosmology of Saint Victorinus of Poetovio: from the Creation of Light to the Creation of Adam - Nikolay A. Khandoga (Warszawskie Studia Teologiczne)
This article reveals the cosmology, or the doctrine of the creation of a little-known holy father and, possibly, the first martyr of the Pannonian province of the Roman Empire – Saint Victorinus of Poetovio (c. 230 - 303/304), the author of the first Latin Six Days. Victorinus, in his original writings - the treatise "On the Creation of the World" and the interpretation of "On Revelation", using various exegetical methods, for example, allegories and typologies - paid particular attention to the meaning and purpose of creation, the first, fourth, fifth and sixth days of creation. As for the second and third days of creation, you need to be an attentive reader in order to find the necessary information in the treatise "On the Creation of the World". At the same time, it should be borne in mind that Victorinus of Poetovio, as a supporter of binitarianism, taught that there is a single God the Creator, or God the Father and God the Son. However, this does not mean that Victorinus did not know anything about the Holy Spirit, since in the treatise "On the Creation of the World" and the interpretation "On Revelation", He is repeatedly mentioned, starting with the events associated with the incarnation of the Son of God into the world. As a result, we learn that the world, or the universe, was created by God in six days from nothing and for the glorification of His greatness by the primordial man, or the first people, the primordial and other angels, as well as animals. In addition, the uniqueness of this Six Days lies in the fact that Victorinus of Poetovio, when writing it, used not only the Holy Scriptures and Holy Tradition but also repeatedly resorted to the author's innovation.